ESSENCE OF UTC SOCIO-ECONOMIC DEVELOPMENT STRATEGY IN THE CONTEXT OF CHANGING APPROACHES TO REGIONAL DEVELOPMENT IN UKRAINE - Sologub , S.I. (The actual problems of regional economy development, 2021)
The article is aimed at studying the essence of the strategy of socio-economic development of UTC in the context of changing approaches to regional development in Ukraine. The actualization of the need for research and development of a strategy for socio-economic development of UTC is due primarily to the creation of territorial communities and decentralization processes, gaining more power over the allocation and use of community resources. In order to conduct a study on the state of interest of the population in this topic, analytical procedures were performed using Google Trends, which allows identifying the popularity of queries and existing trends. As a result of the conducted graphic analysis of trends, it is established that the value of queries for the word «Strategy» for the last 2 years has stable dynamics. The terms «UTC Strategy» and «UTC Development Strategy» have a single unit meaning of search queries, and the terms «Community Strategy», «UTC Socio-Economic Development Strategy» have zero search dynamics. This situation indicates that UTCs are now in the early stages of their formation and development, and therefore their representatives have not yet fully mastered the necessary tools for effective UTC management. It is established that the studies of UTC strategy are isolated and, in the presence of radical differences from the functioning of enterprises, cannot be used to form a strategy of socio-economic development of UTC. Therefore, the author's vision of the interpretation of the term «UTC strategy» is proposed: it is a long-term plan (program) of territorial community development, which provides a general direction (course, landmark) of territorial community development and a set of consistent actions to ensure its competitiveness and investment attractiveness. It is determined that the strategy of socio-economic development of UTC in the context of changing approaches to regional development in Ukraine: ensures the compatibility of all development plans of the territorial community; coordinates all components of socio-economic development of the territorial community, uniting them into a single whole; is a tool for planning, implementation and control of the general guideline of socio-economic development of the territorial community; is a means to achieve the planned result; is a tool for solving key problems in the local community.